Pendidikan Berbasis Iman Perspektif Yusuf Al-Qaradawy dan Implikasinya bagi Pendidikan Anak dalam Keluarga - Imroatul Istiqomah; Roichan Hibatullah (Program Pascasarjana UNU Surakarta, 2026)
The crisis of faith and morality among children is one of the consequences of the weakening role of family education as the first and primary educational institution. Moreover, the failure of family education directly contributes to the failure of education as a whole, since the family constitutes the foundation for the formation of Muslim personality. This article aims to critically examine the concept of faith-based education in Yusuf al-Qaradawi’s thought and its implications for children’s education within the family. This study employs a qualitative approach using library research, analyzing al-Qaradawi’s major works related to faith, education, and the formation of Muslim personality. The data are analyzed through content analysis with a descriptive-analytical approach. The findings indicate that, according to Yusuf al-Qaradawi, faith-based education positions faith as the fundamental foundation of education, integrally connected with worship and moral conduct. Faith education is not understood merely in doctrinal terms, but as a comprehensive and continuous process of personality development. The implications of this concept for family education emphasize the role of parents as the primary agents in instilling monotheism (tawḥīd), cultivating religious practices, and internalizing moral values in children’s daily lives. This study reinforces the position of family education as a strategic arena for the actualization of faith-based Islamic education in addressing the challenges of children’s education in the contemporary era.